2020
DOI: 10.3892/or.2020.7672
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 7 promotes non‑small cell lung cancer progression by facilitating G1/S phase and epithelial‑mesenchymal transition and activating AKT and ERK1/2 signaling

Abstract: Increasing evidence has indicated the roles of sirtuin 7 (SIRT7) in numerous human cancers. However, the effects and the clinical significance of SIRT7 in human lung cancer is largely unknown. The present research demonstrated that SIRT7 was increased in human lung cancer tumor tissues. SIRT7 upregulation was associated with clinicopathological characteristics of lung cancer malignancy including positive lymph node metastasis, high pathologic stage and large tumor size. SIRT7 was also upregulated in human non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 50 publications
(83 reference statements)
0
13
0
Order By: Relevance
“…NSCLC accounts for a large proportion of cancer-related deaths. 17 Despite the significant advances in the diagnostic and therapeutic techniques of lung cancer in recent decades, treatment results are far from satisfactory. Therefore, there exists an urgent demand for developing effective and safe therapies that target the aggressive progression and metastasis of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…NSCLC accounts for a large proportion of cancer-related deaths. 17 Despite the significant advances in the diagnostic and therapeutic techniques of lung cancer in recent decades, treatment results are far from satisfactory. Therefore, there exists an urgent demand for developing effective and safe therapies that target the aggressive progression and metastasis of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…As a bona fide substrate, the degradation of P27 in nucleus emphasizes SKP2 as a tumor driver, by which it facilitates cell cycle entry and proliferation in many cancers 70 , 71 . Several studies found that SIRT7 overexpression decreases P27 level and accelerates cell proliferation 72 , 73 , supporting SIRT7 as an SKP2 related oncogenic driver. During tumor progression, the majority of SKP2 protein is translocated to cytoplasm, while the function has not been well addressed 70 .…”
Section: Discussionmentioning
confidence: 95%
“…Various studies have demonstrated that EMT is associated with NSCLC progression ( 38 40 ). Interestingly, previous studies have demonstrated that m6A regulators exert crucial roles in the regulation of EMT ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%